2017
DOI: 10.1186/s12903-017-0432-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of severe early childhood caries and associated socioeconomic and behavioral factors in Xinjiang, China: a cross-sectional study

Abstract: BackgroundThis study assessed the prevalence and severity of early childhood caries (ECC) and identified socioeconomic and behavioral correlates of the disease in preschool children living in Xinjiang.MethodsFor this cross-sectional survey, 1727 children aged 3–5 years in Xinjiang were randomly recruited using a three-stage cluster sampling procedure. The “dmft” index according to the WHO 1997 criteria was used to assess ECC and severe ECC (S-ECC). A questionnaire was completed by caregivers. Variables include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
37
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 23 publications
11
37
3
6
Order By: Relevance
“…The results of this study were in accordance with several previous studies [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017]. In Japan, "no residence tax" means low household income.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study were in accordance with several previous studies [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017]. In Japan, "no residence tax" means low household income.…”
Section: Discussionsupporting
confidence: 82%
“…Some previous studies in developing countries reported that risk factors associated with S-ECC were frequent or prolonged breastfeeding [Özen et al, 2016;Feldens et al, 2018], socioeconomic status [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017], not having help with brushing [Turton et al, 2016;Mangla et al, 2017], and snacking habits [Evans et al, 2013;Mangla et al, 2017;Peres et al, 2017;Sun et al, 2017]. However, it is unclear whether these risk factors for S-ECC are similarly associated with S-ECC in developed countries.…”
Section: Introductionmentioning
confidence: 98%
“…Contradictorily, Korea and Hong Kong had very high HDI scores, but their caries prevalence was high (>50%) compared with their counterparts in Europe. Furthermore, 11 studies in Asia reported mean dmft scores equivalent to or higher than 3 . It is noteworthy that the HDI can indicate only the development level of the entire country, and that the socioeconomic status of an individual city or district cannot be reflected in this index, which is a limitation of the present review.…”
Section: Discussionmentioning
confidence: 80%
“…An initial screening of the title and abstract revealed that 551 articles were duplicates and 1707 articles did not meet the inclusion criteria. Full texts of the remaining 152 articles were assessed, and 37 studies were included in the present study . No additional publications were identified from the bibliography of these 152 articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation